KAJIAN MUTU WORTEL (Daucus carota L.) TEROLAH MINIMAL YANG DIKEMAS SECARA VAKUM - Rusni Mirontoneng; Ireine A. Longdong; Lady Lengkey (Universitas Sam Ratulangi, 2019)
ABSTRACTMinimally processing of fresh carrots with vacuum packaging stored in lowtemperatures. The research objective is to assessing the quality of texture, change in weight,color, and moisture content and to determining the shelf life of minimally processed carrotsin vacuum packaging. Carrots were washed, then peeled, cut into pieces with a thickness of0.6 cm, after that rinse with water and chlorine. Then packaged according to treatment(vacuum and without vacuum) with a weight of 100 g each, after that it is stored in arefrigerator that has a temperature of 6 oC - 12 oC. The results showed that the initial watercontent of the sliced carrots day 0 has an average of 89.13%, after the 24 day for vacuumpackaging has an average of 91.13% and the packaging without vacuum has an average of90.87%. The average value of weight loss in vacuum packaging is 0.52%, and packagingwithout vacuum is 1.23%. Average value of texture on the vacuum package was 16.73 N, andthe final value of texture 12.96 N and the average texture value on the packaging withoutvacuum is 0: 17.29 N. After the 24th day is 14.85 N. Color changes on vacuum packs andwithout vacuum start on the 15th day until the 24th day from orange to orange yellow.Keywords: carrot, minimalyl processing, vacuum packaging, quality, low temperature.